If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + x + 2x = -12 Combine like terms: x + 2x = 3x 3 + 3x = -12 Solving 3 + 3x = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3x = -12 + -3 Combine like terms: 3 + -3 = 0 0 + 3x = -12 + -3 3x = -12 + -3 Combine like terms: -12 + -3 = -15 3x = -15 Divide each side by '3'. x = -5 Simplifying x = -5
| 6-8p=35 | | c^2+4bc+3b^2= | | 50-x-3=47-x | | -3w^2+7w-66=0 | | -4x-44=-7x+16 | | 147=7m+7 | | 11+x+x=8x-7 | | -10-12x=-11x+13 | | -10(1-2k)=-5(k-3) | | w-7b=y | | -32+11x=10+8x | | -67+3x=-7x+83 | | -5n-8(7n)=-8 | | (x^2)-kx+196=0 | | -168-x=53+12x | | 18x^2+18x-24=0 | | 4(5x+10)=4(x-6) | | 12x^2-204x+630=0 | | 7x-36=48+11x | | 7+n-2=-5-n | | -16-12x=40-8x | | p+2=-2-3p | | -4p+7=7-4p | | x-77=35-6 | | 2X^2-34X+105=0 | | 0=2m+5m | | 11x-6=-39 | | 15=m-4m | | p-5-3=-9 | | 3x-7+x=10 | | -12=-5b-b | | 2(x+1)-4=5x-3(2+x) |